Demand for the statutory home care scheme - Brendan Walsh; Sean Lyons (The Economic and Social Research Institute (ESRI), 2021)
A statutory scheme for the financing and regulation of home support services is a key Sláintecare reform proposal. An Economic and Social Research Institute report entitled "Demand for the Statutory Home Support Scheme" is the first of three research projects funded by the Department of Health to inform the development of a home support scheme.
Keywords: 330; Häusliche Pflege; Pflegefinanzierung; Sozialreform; Irland